Application of the Perme Score to assess mobility in patients with COVID-19 in inpatient units - Milena Siciliano Nascimento; Claudia Talerman; Raquel A. C. Eid; Simone Brandi; Luana L.S. Gentil; Fernanda M. Semeraro; Fabiano B. Targa (Canadian Journal of Respiratory Therapy)
# Objective